2024
DOI: 10.1021/acsomega.3c07404
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-Induced Stress Enhanced Biomass and Production of High-Value Secondary Cell Products in Submerged Adventitious Root Cultures of Stevia rebaudiana (Bert.)

Bakht Naz,
Aftab Afzal,
Hina Ali
et al.

Abstract: Stress is one of the important factors that directly or indirectly affects the plant architecture, biochemical pathways, and growth and development. Melatonin (MEL) is an important stress hormone; however, the exogenous addition of melatonin to culture media stimulates the defense mechanism and releases higher quantities of secondary metabolites. In this study, submerged adventitious root cultures (SARCs) of diabetically important Stevia rebaudiana were exposed to variable concentrations (0.5−5.0 mg/L) of MEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The concentration of secondary metabolites in the leaves of stevia varies significantly in heterogenous populations. Infertility and low viability of seeds, as well as poor performance of stem cuttings used in clonal propagation, are major issues limiting the production of homogenous population of Stevia 18 , 19 . Exposure of plants grown in vitro to biotic or abiotic elicitors has been shown to modulate the biosynthetic pathways for certain plant metabolites, often releasing higher quantities of valuable metabolites in less time 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of secondary metabolites in the leaves of stevia varies significantly in heterogenous populations. Infertility and low viability of seeds, as well as poor performance of stem cuttings used in clonal propagation, are major issues limiting the production of homogenous population of Stevia 18 , 19 . Exposure of plants grown in vitro to biotic or abiotic elicitors has been shown to modulate the biosynthetic pathways for certain plant metabolites, often releasing higher quantities of valuable metabolites in less time 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Elicitation is an effective tool to not only activate plant defence mechanisms, but to release highly valuable secondary metabolites such as those used in the pharmaceutical, agrochemical, bio-pesticide, cosmetic, and food additive industries 22 . The study of elicitor activity plays an important role in elucidating plant defence mechanisms, as well as the regulation and prospects for enhancing the production of valuable secondary metabolites 18 . The main aim of the study reported here is to report the effect of the potential elicitors gibberellic acid GA 3 (growth regulator), NaCl (ionic and osmotic stress), and polyethylene glycol (osmotic stress) on shoot morphogenesis, polyphenolics content, antioxidant activity, and proline and stevioside content in shoots of Stevia rebaudiana cultured in vitro.…”
Section: Introductionmentioning
confidence: 99%